2018
DOI: 10.1158/1538-7445.am2018-2928
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2928: Bortezomib sensitizes glioblastoma with unmethylated MGMT promoter to temozolomide-chemotherapy through MGMT depletion and abrogated autophagy flux

Abstract: Background: Glioblastoma with unmethylated O6-methyl guanine DNA methyltransferase (MGMT) promoter is highly resistant to temozolomide (TMZ) chemotherapy. Strategies that ameliorate drug resistance are sorely needed. Recent trials of the proteasome inhibitor bortezomib (BTZ) (Velcade) in combination with various drugs failed due to inappropriate schedule timing and dosing. We hypothesized that pretreatment with BTZ prior to TMZ administration may sensitize glioblastoma cell to TMZ chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…7), promoting ATM/Chk2 mediated DNA damage signaling and activating p53-mediated G2/M cell cycle arrest 63 . As we recently demonstrated 59 , BTZ also depleted MGMT protein and mRNA, an additional mechanism that synergized with TMZ to effectively kill GBM cells by enhanced programmed cell death. We anticipate to uncover similar mechanisms of efficacy in the patients undergoing treatment in our phase II clinical trial, NCT03643549 (www.clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…7), promoting ATM/Chk2 mediated DNA damage signaling and activating p53-mediated G2/M cell cycle arrest 63 . As we recently demonstrated 59 , BTZ also depleted MGMT protein and mRNA, an additional mechanism that synergized with TMZ to effectively kill GBM cells by enhanced programmed cell death. We anticipate to uncover similar mechanisms of efficacy in the patients undergoing treatment in our phase II clinical trial, NCT03643549 (www.clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 57%
“…Another mechanism of TMZ resistance in GBM patients is represented by unmethylated MGMT promoter tumors 58 , where the enzyme and proficiently repairs the chemotherapy-induced DNA damage but the cells maintain a high apoptosis threshold. We recently showed that BTZ treatment depletes MGMT protein and mRNA and sensitizes GBM cells to TMZ chemotherapy 59 . In conclusion, BTZ augmented cell death of TMZ resistant tumor cells by accumulating autophagosomes as a result of abrogated autophagic flux (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected due to the BTZ's ability to inhibit the MGMT activity in T98G cells, leading to an increased antiproliferative activity. 8,49 The improved anticancer activity in the MGMT-negative U251 cells can also be explained because BTZ possesses antiproliferative activity by its own (BTZ's survival inhibition curves in Figure S7 in the Supporting Information). Furthermore, we observed a significant reduction in the TMZ concentration required to achieve the same level of survival inhibition when combined with BTZ.…”
Section: Physicochemical Properties Of Tf-mentioning
confidence: 99%
“…Therefore, these trials are not using the optimal schedule identified here. Expanded access would be justified by the lack of long-term effective treatments for this lethal disease [62], and could employ our optimal schedule. Even so, one limitation of our modelling approach should be emphasized: our model incorporates synergistic effectiveness between TMZ and MGMT/APNG inhibition, but does not include synergistic toxicity.…”
Section: Potential For Clinical Translationmentioning
confidence: 99%